I Like the Way You Eat It: Lemur (Indri indri) Gut Mycobiome and Geophagy - Borruso, Luigimaria; Checcucci, Alice; Torti, Valeria; Correa, Federico; Sandri, Camillo; Luise, Daine; Cavani, Luciano; Modesto, Monica; Spiezio, Caterina; Mimmo, Tanja; Cesco, Stefano; Di Vito, Maura; et al. (Microbial ecology, 2021)
Here, we investigated the possible linkages among geophagy, soil characteristics, and gut mycobiome of indri (Indri indri), an endangered lemur species able to survive only in wild conditions. The soil eaten by indri resulted in enriched secondary oxide-hydroxides and clays, together with a high concentration of specific essential micronutrients. This could partially explain the role of the soil in detoxification and as a nutrient supply. Besides, we found that soil subject to geophagy and indris’ faeces shared about 8.9% of the fungal OTUs. Also, several genera (e.g. Fusarium, Aspergillus and Penicillium) commonly associated with soil and plant material were found in both geophagic soil and indri samples. On the contrary, some taxa with pathogenic potentials, such as Cryptococcus, were only found in indri samples. Further, many saprotrophs and plant-associated fungal taxa were detected in the indri faeces. These fungal species may be involved in the digestion processes of leaves and could have a beneficial role in their health. In conclusion, we found an intimate connection between gut mycobiome and soil, highlighting, once again, the potential consequent impacts on the wider habitat.